Granger Causality-based Information Fusion Applied to Electrical Measurements from Power Transformers. - Rodríguez-Rivero, Jacob; Ramírez, Javier; Martínez-Murcia, Francisco Jesús; Segovia, Fermín; Ortiz-García, Andrés; Salas-González, Diego; Castillo-Barnes, Diego; Álvarez-Illán, Ignacio; Puntonet, Carlos; Jiménez-Mesa, Carmen; Leiva, Francisco J.; Carrillo, Susana; et al. (Elsevier, 2019)
In the immediate future, with the increasing presence of electrical vehicles and the large increase in the use of renewable energies, it will be crucial that distribution power networks are managed, supervised and exploited in a similar way as the transmission power systems were in previous decades. To achieve this, the underlying infrastructure requires automated monitoring and digitization, including smart-meters, wide-band communication systems, electronic device based-local controllers, and the Internet of Things. All of these technologies demand a huge amount of data to be curated, processed, interpreted and fused with the aim of real-time predictive control and supervision of medium/low voltage transformer substations. Wiener–Granger causality, a statistical notion of causal inference based on Information Fusion could help in the prediction of electrical behaviour arising from common causal dependencies. Originally developed in econometrics, it has successfully been applied to several fields of research such as the neurosciences and is applicable to time series data whereby cause precedes effect. In this paper, we demonstrate the potential of this methodology in the context of power measures for providing theoretical models of low/medium power transformers. Up to our knowledge, the proposed method in this context is the first attempt to build a data-driven power system model based on G-causality. In particular, we analysed directed functional connectivity of electrical measures providing a statistical description of observed responses, and identified the causal structure within data in an exploratory analysis. Pair-wise conditional G-causality of power transformers, their independent evolution in time, and the joint evolution in time and frequency are discussed and analysed in the experimental section.
Keywords: Análisis de series temporales; Sistemas electroenergéticos; Granger causality; Power transformers; Functional connectivity; SCADA measurements; Time series analysis